Social-cognitive process in posttraumatic stress disorder in motor vehicle accident survivors. - Miller, Lynn. (University of Ottawa (Canada), 2000)
Posttraumatic stress disorder (PTSD) is a common sequela in those individuals who survive or witness an event such as a motor vehicle accident (MVA) that may threaten personal and interpersonal integrity. Yet, not all individuals who experience MVAs develop PTSD. It was hypothesized that MVA survivors who developed PTSD would evidence dysfunctional thinking characterized by maladaptive rules, assumptions, and interpretations, or schema specific to road traffic situations. Such dysfunctional thinking patterns were thought to be associated with individuals' perceptions of increased threat in road traffic situations and with PTSD in survivors of MVAs. The study also sought to explore the possible modifying effect that social interactional influences may have on maladaptive schema. In Study 1, a Motor Vehicle-Related Schema (MVRS) questionnaire was developed as A tool to tap the content of a potential dysfunctional thought process germane to road traffic situations. In Study 2, MVA survivors who developed PTSD were compared to MVA survivors who did not develop PTSD. A group of injured workers and a community sample were used as control groups. The control groups allowed the researcher to address the question of specificity of maladaptive schema related to road traffic situations in the MVA PTSD group. Multiple measures were used to assess the presence or absence of PTSD. Participants in the MVA PTSD group endorsed significantly higher levels of dysfunctional and maladaptive cognitions specific to road traffic situations than did all other participant groups. Given that other factors might influence this type of thought process, a number of other variables were examined. The findings remained robust even after adjustment for: (a) persistent dysfunctional schemas tapping general personal and interpersonal vulnerability, (b) subjective pain, and (c) self-reported depression. In addition, MVA survivors who developed PTSD, compared to MVA survivors who did not develop PTSD, reported significantly lower levels of perceived beneficial social interactions. However, these findings became non-significant after adjustment for subjective pain and self-reported depression. Overall, the findings suggest that MVA survivors who developed PTSD organized and interpreted stimuli relevant to road traffic situations in ways that were fundamentally different from MVA survivors who did not develop PTSD, injured workers and a community sample. More specifically, participants in the MVA PTSD group tended to interpret road traffic situations as more threatening than did participants in the other groups in this study. The perception of lower levels of beneficial social interactions appear to be associated more with heightened levels of distress, pain, and depression than with PTSD. This investigation demonstrates that it is possible to tap into maladaptive schemas using a self-report measure. Consistent with cognitive-behavioral clinical protocols for MVA survivors with PTSD, these results support the notion that specific dysfunctional or maladaptive cognitions appear to characterize MVA survivors with PTSD. A better understanding of dysfunctional schemas specific to road traffic situations, gleaned through further research, may be of some benefit in attenuating or managing symptoms of PTSD in WA survivors. Although the injured workers were not the focus of this research, many of the participants in this group met the classification for PTSD or posttraumatic stress symptoms (PTSS). This finding suggests that clinical screening and further research for PTSD in injured workers might also be warranted.
Keywords: Psychology, Clinical.